PERAN GURU DALAM MENANAMKAN NILAI TANGGUNG JAWAB DI SEKOLAH DASAR - Herly Yuniarti; Haifaturrahmah; Inang Irma Rezkillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Character education is an important foundation in shaping a generation with noble and responsible character. Teachers have a central role in instilling the value of responsibility through role models, habituation, and meaningful learning in elementary schools. This study aims to analyze the role of teachers in instilling the value of responsibility and the factors that influence its success. The method used is a library research with a qualitative descriptive approach to ten journal articles on character education and the role of teachers in elementary schools. The results show that teachers act as role models, guides, motivators, and evaluators in shaping students' responsible character. Supporting factors include a conducive school environment, parental support, and positive habits, while obstacles that arise include low student awareness and external environmental influences. In conclusion, the role of teachers is not only focused on the transfer of knowledge, but also the formation of personality through role models and the continuous habituation of the value of responsibility.